Racial disparities in discontinuation of long-term opioid therapy following illicit drug use among black and white patients. (1st November 2018) - Gaither, Julie R.; Gordon, Kirsha; Crystal, Stephen; Edelman, E. Jennifer; Kerns, Robert D.; Justice, Amy C.; Fiellin, David A.; Becker, William C.
Highlights: Urine drug testing is recommended for all patients receiving opioid therapy. Whites are at higher risk of opioid overdose. Yet blacks are more likely to receive urine drug testing (UDT). Blacks are more likely to have opioids discontinued following a positive UDT. A more universal approach to urine drug testing is needed. Abstract: Background: Among patients prescribed long-term opioid therapy (LTOT) for chronic pain, no study has yet examined how clinicians respond to evidence of illicit drug use and whether the decision to discontinue opioids is influenced by a patient's race. Methods: Among outpatients of black and white race initiating LTOT through the VA between 2000 and 2010, we reviewed electronic medical records to determine whether opioids were discontinued within 60 days of a positive urine drug test. Logistic regression was used to examine differences by race. Results: Among 15, 366 patients of black (48.1%) or white (51.9%) race initiating LTOT from 2000 to 2010, 20.5% (25.5% of blacks vs. 15.8% of whites, P <. 001) received a urine drug test within the first 6 months of treatment; 13.8% tested positive for cannabis and 17.4% for cocaine. LTOT was discontinued in 11.4% of patients who tested positive for cannabis and in 13.1% of those who tested positive for cocaine. Among patients testing positive for cannabis, blacks were 2.1 times more likely than whites to have LTOT discontinued (adjusted odds ratio [AOR] 2.06, 95% confidence interval [CI] 1.04–4.08). Among patients testing positive for cocaine, blacks were 3.3 times more likely than whites to have LTOT discontinued (AOR 3.30, CI 1.28–8.53). Conclusions: Among patients testing positive for illicit drug use while receiving LTOT, clinicians are substantially more likely to discontinue opioids when the patient is black. A more universal approach to administering and responding to urine drug testing is urgently needed.